The Influence of Individual Characteristics, Job Characteristics and Organizational Culture on Employee Performance Mediated By Job Satisfaction : (Study on Inseminators of Animal Husbandry and Fisheries Department of Blora Regency) - Tisnawati, Ruri; Lukiastuti, Fitri (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
This study aims to determine how much influence of individual characteristics, job characteristics and organizational culture on employeeperformance mediated by job satisfaction of inseminators of Animal Husbandry and Fisheries Department of Blora Regency(DINAKIKAN). The data used is the data by distributing questionnaires to 69 inseminators of Dinakikan of Blora Regency. Toanalyse the data, statistical analysis used structure equation modelling (SEM) and processed with Smart PLS application. The resultshows that organizational culture has no effect on job satisfaction. Organizational culture has a positive influence on employeeperformance. Individual characteristics have a positive influence on job satisfaction. Individual characteristics have a positive influence onemployee performance. Job characteristics have a positive influence on job satisfaction. Job characteristics do not have a positive influence onemployee performance. Job satisfaction has a positive influence on employee performance. Job satisfaction is able to mediate the relationshipbetween job characteristics and employee performance. Job satisfaction is not able to mediate the relationship between individualcharacteristics t and employee performance. Job satisfaction is not able to mediate the relationship between organizational culture andemployee performanceKeywords: Individual Characteristics, Job Characteristics, Organizational Culture, Job Satisfaction, Employee Performance